2005
DOI: 10.1152/jn.00320.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual Interference in Rapid Discrete Movements Is Task Specific and Occurs at Multiple Levels of Processing

Abstract: Obhi, Sukhvinder S. and Melvyn A. Goodale. Bimanual interference in rapid discrete movements is task specific and occurs at multiple levels of processing . J Neurophysiol 94: 1861-1868, 2005. First published May 25, 2005 10.1152/jn.00320.2005. It has been suggested that interference in symbolically cued bimanual reaction time tasks is caused primarily by the perceptual processing of stimuli and not by motor preparation of the required movements. Here subjects made movements of the right and left index fingers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The frequency dependency of the RT and MT is consistent with research that has shown that either or both slow down the more in the presence of a second task, the more the latter differs from the first in terms of movement amplitude and/or accuracy, movement direction or peak force (Heuer & Klein, 2006;Kelso, Southard, & Goodman, 1979;Marteniuk & MacKenzie, 1980;Marteniuk, MacKenzie, & Baba, 1984;Obhi & Goodale, 2005;Spijkers & Heuer, 2004;Weigelt, 2007). Although the movements here studied did not significantly differ in amplitude 7 across frequencies and positions, they were distinct in terms of their underlying dynamics as well as in terms of their time scale of operation.…”
Section: Discussionsupporting
confidence: 87%
“…The frequency dependency of the RT and MT is consistent with research that has shown that either or both slow down the more in the presence of a second task, the more the latter differs from the first in terms of movement amplitude and/or accuracy, movement direction or peak force (Heuer & Klein, 2006;Kelso, Southard, & Goodman, 1979;Marteniuk & MacKenzie, 1980;Marteniuk, MacKenzie, & Baba, 1984;Obhi & Goodale, 2005;Spijkers & Heuer, 2004;Weigelt, 2007). Although the movements here studied did not significantly differ in amplitude 7 across frequencies and positions, they were distinct in terms of their underlying dynamics as well as in terms of their time scale of operation.…”
Section: Discussionsupporting
confidence: 87%
“…This notion of a special status of end positions in an array, which may act as natural spatial anchors that facilitate spatial processing, is supported by the well-known finding that a masking stimulus has less effect on location information at end positions than at middle positions of an array of letters (e.g., Mewhort & Campbell, 1978). In addition, Obhi and Goodale (2005) recently made a similar point by showing that landmarks, once encoded, facilitate pointing movements and reduce error variability. The outcome of this particularly salient spatial coding of end positions is that movements can be made more rapidly to such locations without a corresponding change in accuracy.…”
Section: Discussionmentioning
confidence: 84%
“…Whereas there is large body of research on the production and control of human action, there is less work devoted to understanding the subjective experience of action (Rosenbaum, 1991 ; Haggard, 2001 ; Obhi and Goodale, 2005 ). The sense of agency refers to the feeling of control over self-produced actions and, as a consequence, the feeling of being a causal agent capable of effecting change in the environment (Gallagher, 2012 ; Moore and Obhi, 2012 ).…”
Section: Introductionmentioning
confidence: 99%